2013
DOI: 10.1103/physrevd.88.085014
|View full text |Cite
|
Sign up to set email alerts
|

Lee-Wick standard model at finite temperature

Abstract: The Lee-Wick Standard Model at temperatures near the electroweak scale is considered, with the aim of studying the electroweak phase transition. While Lee-Wick theories possess states of negative norm, they are not pathological but instead are treated by imposing particular boundary conditions and using particular integration contours in the calculation of S-matrix elements. It is not immediately clear how to extend this prescription to formulate the theory at finite temperature; we explore two different pictu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Tetraquark states in the large N c limit of QCD has been explored in Refs. [19][20][21], which indicates that a compact tetraquark meson may have narrow decay widths which scale as 1/N c . This gives reasonable candidates for the additional spectroscopic hadron series apart from the quark model.…”
mentioning
confidence: 99%
“…Tetraquark states in the large N c limit of QCD has been explored in Refs. [19][20][21], which indicates that a compact tetraquark meson may have narrow decay widths which scale as 1/N c . This gives reasonable candidates for the additional spectroscopic hadron series apart from the quark model.…”
mentioning
confidence: 99%
“…Grinstein, et al [6] also demonstrated that the scattering of longitudinally polarized massive vector bosons satisfied perturbative unitarity. Explicitly, they later showed that unitarity and Lorentz-invariance are preserved in the S-matrix to all orders and that causality arises as an emergent macroscopic phenomenon [7].Since the Grinstein et al papers, there have been numerous phenomenological studies of the LWSM, including, but not limited to the study the possibility of observing the microcausality violation at colliders [8][9][10][11][12][13], the effects of the LWSM on precision electroweak measurements [14][15][16][17][18][19], and finite temperature effects [20][21][22]. The LW partners of the light quarks and gluons must be relatively heavy, O(10) TeV, in order to avoid detection.…”
mentioning
confidence: 99%